A pseudoduplication in Lycopersicon pimpinellifolium - Rick, Charles M. (1979)
A double-banded variant of Prx-2 encountered in a single wild plant in a previous survey of the peroxidases of Lycopersicon pimpinellifolium was subjected to genetic analysis. Segregations obtained from crosses of this true-breeding type with various alleles of Prx-2 yielded anomalous segregations that are not compatible with a single locus model and suggest activity of alleles of a gene at another, independent locus. A critical test was afforded by studying simultaneous segregation for the apparent duplication and for two alleles at the neighboring Prx-3, a gene which proves to be very tightly linked with Prx-2. The results of the new test revealed independence between the double-banded type and Prx-3, hence also between the former and Prx-2. The most tenable hypothesis stipulates that an independent gene mPx2(1) modifies post-translationally the product coded by Prx-2(+) to yield two electrophoretically separable isozymes. These results reveal the risk of assuming, without appropriate genetic tests, that gene duplication is necessarily the cause of multiple banding.